Prediction of postoperative lower respiratory tract infections in tongue cancer patients based on pretreatment swallowing function. (13th January 2020) - Deng, Wei; Yang, Le; Xie, Chunqing; Lu, Huanzi; Xiao, Yudong; Zeng, Bin; Liang, Yujie; Liao, Guiqing
Abstract: Objectives: This study investigated the predictive role of pretreatment swallowing function and surgical factors on postoperative and nosocomial lower respiratory tract infections (PN‐LRTIs). Subjects and methods: A retrospective study for predicting PN‐LRTIs from January 2017 to December 2018 at Hospital of Stomatology, Sun Yat‐sen University. Patients who were newly diagnosed with tongue squamous cell carcinoma (TSCC) were enrolled. Presurgical swallowing function was assessed using water swallow test (WST) and the M.D. Anderson Dysphagia Inventory (MDADI). Results: A total of 83 patients were recruited to the study. Of which 54 were men (65.1%) and 29 were women (34.9%), with the mean age of 51 years old. Thirteen (15.7%) developed PN‐LRTIs. On univariate analysis, the outcomes of WST, the MDADI scores, T stage, tongue resection range, operative time, segmental mandibulectomy, and type of neck dissection exhibited a statistical significance ( p < .05). On multivariate analysis, abnormal group of WST (odds ratio [OR], 15.88; 95% CI, 2.13–118.64) and total glossectomy (OR, 12.20; 95% CI, 2.01–68.32) was demonstrated to be independent risk factors. Conclusions: The WST together with the resection range of tongue can predict the postoperative risk of PN‐LRTIs collaboratively. Clinically, preventive measures and intensified care should be taken for patients with abnormal WST outcome before surgery and management of total glossectomy.